2010
DOI: 10.1177/0310057x1003800624
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin to Control an Incapacitating Tic in a Child with a Clavicular Fracture

Abstract: We present the case of an 11-year-old boy who suffered from an undefined tic disorder and incidentally sustained a traumatic fracture of the clavicle. The fracture healing course was complicated by the tic activity, and the frequency and intensity of the tics were worsened by the presence of clavicular pain. He underwent surgery and his management required the collaboration of orthopaedic surgeons, the Acute Pain Service, neurologists for tic management and rehabilitation physicians who performed the intramusc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…One goal of the multidisciplinary approach is to provide a more holistic and individualized approach to care, addressing current challenges and anticipating future situations. For instance, Chen et al 35 reported on a patient managed mainly by psychology without pharmacologic therapy despite the progression of tics, which were described as slow writhing movements involving his neck and shoulder muscles. This culminated in an acute presentation with a clavicular fracture.…”
Section: Resultsmentioning
confidence: 99%
“…One goal of the multidisciplinary approach is to provide a more holistic and individualized approach to care, addressing current challenges and anticipating future situations. For instance, Chen et al 35 reported on a patient managed mainly by psychology without pharmacologic therapy despite the progression of tics, which were described as slow writhing movements involving his neck and shoulder muscles. This culminated in an acute presentation with a clavicular fracture.…”
Section: Resultsmentioning
confidence: 99%
“…White et al described the use of botulinum toxin as an adjunct therapy in a case of a periprosthetic scapular spine fracture, whereby the botulinum toxin was injected into the deltoid muscle to reduce potential strain from the muscle on the surrounding fracture site [ 23 ]. Chen and Thalayasingam reported a case of botulinum toxin use in a child with a clavicular fracture and motor tic disorder to control the pain at the fracture site caused by the tics, as well as provide adequate immobilization of the fracture for healing [ 17 ]. In a case series by Shilt et al, botulinum toxin was utilized in 5 male patients to achieve controlled immobilization and prevention of tendon repair failure following proximal hamstring avulsion repair [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another animal study, rat femur fractures experienced increased biomechanical and histopathologic healing when treated with botulinum toxin A compared to no treatment, though the fracture callus diameter was smaller [ 14 ]. In one of the few clinical case reports on the topic, a patient with an undefined tic disorder sustained clavicle fracture treated with surgical fixation and botulinum toxin A injection, ultimately allowing fracture union without complication [ 15 ]. Finally, a retrospective review by Freibott et al [ 16 ] demonstrated the clinical utility of botulinum toxin injections in the treatment of post-traumatic elbow stiffness caused by heterotopic ossification.…”
Section: Discussionmentioning
confidence: 99%